T1 Hyperintense Vertebral Column Melanoma Metastases - McMenamin, D.S.; Stuckey, S.L.; Potgieter, G.J. (American Journal of Neuroradiology, 2007)
SUMMARY: We report a case of T1 hyperintense vertebral column metastatic disease in a 24-year-old man with metastatic melanoma. Radiologic work-up revealed multiple lytic vertebral metastases on CT with corresponding T1 hyperintensity on MR imaging. Whereas T1 hyperintensity associated with melanoma has been well documented, to our knowledge, this is the first described case of widespread T1 hyperintense metastatic bone disease. T1 hyperintense bone lesions are virtually always benign. However, correlation with the lesion appearances on other MR imaging sequences and imaging modalities as well as with the clinical history may occasionally suggest otherwise.